Taxonomic revision of the genus Anomalophylla Reitter, 1887 (Coleoptera: Scarabaeidae: Melolonthinae: Sericini) - Ahrens, Dirk (Zootaxa, 2005)
The species of the genus Anomalophylla Reitter, 1887 are revised. Eighteen new species are described: Anomalophylla dongchuanensis, A. ganhaiziensis, A. hispidulosa, A. huashanica, A. kangdingensis, A. liciata, A. majori, A. morula, A. moxiensis, A. obscuripennis, A. plagipennis, A. qinlingensis, A. stoetzneri, A. subcarinata, A. subfastuosa, A. tsangpoana, A. vidua, and A. wulingshanica. The formerly unavailable name A. moupinea ab. bicolor Balthasar (1932) was made available as a name for a proper species, A. bicolor. Lectotypes are designated for the following taxa: Anomalophylla kozlovi Medvedev, 1952; A. moupinea Fairmaire, 1891; A. tristicula Reitter, 1887; and Melaserica thibetana Brenske, 1897. One new combination is necessary: Anomalophylla mawi (Arrow, 1946). Homaloplia discoidalis Fairmaire, 1897, is placed in synonymy with A. tristicula Reitter, 1887.